Robot-assisted sacro(hystero)colpopexy with anterior and posterior mesh placement: impact on lower bowel tract function and clinical outcomes at mid-term follow-up - Vincenzo Li Marzi; Simone Morselli; Fabrizio Di Maida; Stefania Musco; Luca Gemma; Francesco Bracco; Riccardo Tellini; Gianni Vittori; Andrea Mari; Riccardo Campi; Marco Carini; Sergio Serni; et al. (Therapeutic Advances in Urology, 2022)
Background: Robotic sacrocolpopexy (RSCP) is an established option for the treatment of apical, anterior, and proximal posterior compartment pelvic organ prolapses (POP). However, there is lack of evidence investigating how lower bowel tract symptoms (LBTS) may change after RSCP. Methods: Data from consecutive patients treated with RSCP for stage 3 or higher POP from 2012 to 2019 at a single tertiary referral center with at least 1 year of follow-up were prospectively collected and retrospectively analyzed. RSCP was performed following a standardized technique which always employed both anterior and posterior hand-shaped meshes. Outcomes were collected at follow-up and analyzed. LBTS were evaluated through the Wexner questionnaire. Results: Overall, 114 women underwent RSCP. Eleven were excluded for missing data, whereas 12 had insufficient follow-up. Thus, 91 (79.8%) patients were included in this cohort. Median follow-up was 42 [interquartile range (IQR), 19–62] months. Mean age was 65 ± 10 years. In our series, RSCP was mainly performed for anterior and apical/medium stage 3 POP (in 95.6% of patients). Anatomic success rate of RSCP was 97.8%, with 89 patients with POP stage 0–1 at 12-month follow-up. Two patients (2.2%) experienced POP recurrence and were treated with redo-SCP. No patient experienced clinically significant posterior vaginal wall prolapse after RSCP. When analyzing LBTS, there was no significant change in postoperative total Wexner’s score as compared to the preoperative value ( p  > 0.05). However, the manual assistance subscore was statistically significantly lower within the first-year follow-up ( p  = 0.04), but it spontaneously improved during the follow-up ( p  = 0.12). Conclusion: RSCP with simultaneous placement of both anterior and posterior mesh is safe and successful to treat high-stage POP in carefully selected patients. Of note, LBTS appear unaffected by posterior mesh placement, supporting its routine use to prevent posterior POP recurrence. Larger prospective studies are needed to confirm our results.